Psychiatric Victims of Human Experiments under National Socialism - Weindling, P. (Die Psychiatrie, 2010)
This paper considers whether it is right to identify by name victims of experiments abused either for psychiatric research, or for other types of experimentation in psychiatric hospitals and institutions. Similar questions arise as to whether it is possible to identify any of the persons for whom brains and other body parts were held for medical research and teaching.
Keywords: Euthanasia; Aktion T4; Human experimentation; National Socialist medicine; Carl Schneider